Original paper Immunoreactivity of transglutaminase cross-linked milk proteins in fermented milk product obtained with Lactobacillus acidophilus - Wróblewska, Barbara; Kaliszewska, Anna; Malinowska, Elżbieta; Troszyńska, Agnieszka (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2011)
Introduction : Milk fermented beverages, such as yoghurt, kefir or others obtained with probiotic cultures, are regarded as products with lower antigen potential than milk and therefore they can be included in the diet for cow’s milk allergic patients. Lactic acid bacteria (LAB) are claimed to have proved immunomodulating effects. Several LAB strains possess the documented ability to modulate immune host responses, and can also stimulate antibody production and macrophage activity, inhibit intestinal inflammation, and alleviate allergic disease symptoms and autoimmune disorders. Particular microbial strains change the immunoreactivity of cow milk proteins to a varied extent. Addition of cross-linked microbial transglutaminase (m-TG) during production of a fermented milk beverage can make proteins and peptides linked engaging epitopes sites, thus reducing their immunoreactive potential. Aim : The aim of the study was to reduce the immunoreactivity of milk proteins (-lactoglobulin, a-lactalbumin, casein fractions) present in dairy products obtained with Lactobacillus acidophilus and improve the sensory quality of products fermented with lactic acid bacteria with the addition of microbial transglutaminase (m-TG). Material and methods : Fermented dairy product samples, with and without m-TG, were produced in Danisco Biolacta Company (Olsztyn). Immunoreactivity was examined using polyclonal antibodies directed to a-casein, -casein, k-casein, a-la, and -lg from our own collection by competitive ELISA. Immunoblot was performed with pooled human sera. The study design was approved by the Medical Research Ethics Committee (30/2009) from the Medical University of Warsaw, Poland. The overall sensory quality of the samples was estimated by the trained panellists of the Sensory Laboratory of the Institute of Animal Reproduction and Food Research of the PAS, Olsztyn. Results : The application of L. acidophilus in fermented milk production allowed reduction of the immunoreactivity of major milk allergens, a-casein, -lactoglobulin, which additionally was reduced as a result of cross-linked reaction with m-TG and the 30 days of storage. The immunoblot revealed the specific reaction between milk proteins with high molecular weight (66-80 kDa) and 29 kDa and specific IgE antibodies of cow milk allergic patients. Conclusions : It can be concluded that application of L. acidophilus strain and addition of m-TG during the technological process can yield a cow milk beverage with low antigen potential. Moreover, the product with m-TG was characterized by a more palatable quality than those obtained without m-TG. The more allergenic proteins were proved to BSA, lactoferrin and a-casein.